KERUSAKAN GIGI MERUPAKAN FOKAL INFEKSI PENYEBAB TIMBULNYA PENYAKIT SISTEMIK - I Gusti Agung Ayu Putu Swastini (Jurnal Kesehatan Gigi (Dental Health Journal), 2013)
Focal infection is a center or an area inside the body, where genns or bacilli of geftns can be spread further to other places in the body and cen cause diseaseThe main cause of infection of the gums and other supporting tissues of the teeth is assembled on the surface of microorganisms teeth (plaqtte bacteria).Hypocrates I920, The spread oJ'infection Jront the primury focus to another ccul talre ploce in set'eral w-als, namely transmission throug/t bloocl ciruiation (haematogenous), transmission through the lymphaticflow (imfogen.), expansion of the infection in the tissue, and spread of gastrointestinal and respiratory tract caused by ingestion or teraspirasinya infective material-systemic diseases that have a direct connection with abnormalities of teeth and tooth supporting tissues, such as cardiovascular disease, allergies, asthma, hay fever disease anemia, diabetes mellitus, arthritis, bladder cancer etc.The conclusion is rhe conclusion is focal infection is closely related to the teeth, which will affect the function of one sttch systemic circulatory system, skeletal ond nervous systems. This is caused by the spread of microorganisms or toxins that can be derived from teeth, tooth root, or infected gums.